2015
DOI: 10.1111/tri.12684
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into pretransplant allosensitization in heart transplant recipients in the contemporary era of immunosuppression and rejection surveillance

Abstract: SummarySolid-phase assays (SPA) have facilitated detection and definition of antibodies to human leukocyte antigens (HLA) and major histocompatibility complex class I chain-related antigen A (MICA). However, clinical consequences of pretransplant SPA results in heart transplantation have been studied insufficiently in the current era of immunosuppression and rejection surveillance. Pretransplant sera, panelreactive antibodies (PRA), pretransplant crossmatch, and clinical data were retrospectively analyzed in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…ACHD patients were more likely to have a PRA of >80%. A study by Svobodova et al 16 found that preformed DSA and elevated peak PRA were independent predictors of antibody‐mediated rejection. We however did not find an increased mortality due to rejection‐mediated causes, possibly due to the limitations of a registry analysis and missing data.…”
Section: Discussionmentioning
confidence: 99%
“…ACHD patients were more likely to have a PRA of >80%. A study by Svobodova et al 16 found that preformed DSA and elevated peak PRA were independent predictors of antibody‐mediated rejection. We however did not find an increased mortality due to rejection‐mediated causes, possibly due to the limitations of a registry analysis and missing data.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, high titer DSA (>1:16) has been associated with complement-fixing reactivity ( 7 , 20 ) and has been used to determine unacceptable HLA antigens for sensitized candidates ( 5 ). DSA determination by SPA and elevated peak panel-reactive antibodies (PRA) were independent predictors of pAMR in an adult cohort of heart transplant recipients ( 21 ). In this study focusing on pretransplant samples, increasing numbers of DSAs and the mean cumulative MFI of DSAs were associated with risk of AMR, and the subset of C1q-reactive DSAs were less informative ( 21 ).…”
Section: Adult Htmentioning
confidence: 99%
“…DSA determination by SPA and elevated peak panel-reactive antibodies (PRA) were independent predictors of pAMR in an adult cohort of heart transplant recipients ( 21 ). In this study focusing on pretransplant samples, increasing numbers of DSAs and the mean cumulative MFI of DSAs were associated with risk of AMR, and the subset of C1q-reactive DSAs were less informative ( 21 ). Pathologic classification of AMR in 37 EMB correlated with circulating DSA and endothelial activation ( 22 ).…”
Section: Adult Htmentioning
confidence: 99%
“…Of those, 73.1% were C1q+, leading them to suggest that by using C1q, CDC XM could be safely eliminated and replaced by VXM resulting in less shipment of donor material, shorter CIT, less DGF, and fewer false-positive XMs while not disqualifying highly sensitized patients. A single study of pretransplant allosensitization and outcomes in sensitized and unsensitized heart recipients [ 19 ] found no association of C1q with AMR, but the authors noted that a prospective negative CDC XM was required that likely eliminated any preformed C1q+ DSA patients.…”
Section: Pretransplantmentioning
confidence: 99%